PEMBERDAYAAN AGEN STATISTIK DALAM MENDUKUNG UPAYA PENINGKATAN LITERASI DAN DIGITALISASI DI DESA REBO - Dalimunthe, Desy Yuliana; Endraswari, Putri Mentari; Julia, Julia; Nurhamidah, Rahma; Purwasih, Ratih (Universitas Mataram, 2024)
The village is a strategic position to support the success of community development programs. Developing and increasing literacy in rural areas faces quite a few challenges. The low level of public education, limited access to reading materials and the lack of educational facilities and infrastructure are often the main obstacles. This community partnership empowerment scheme focuses on the role and function of statistical agents in assisting in the creation of population statistics infographic designs and village potential graphic designs using the Canva application which is guided directly by the Central Statistics Agency (BPS) of the Bangka Belitung Islands Province. This aims at the process of implementing data digitization, especially population statistics data through infographic design. 10 out of 11 statistical agents who took part in training in making infographic designs and filled out pre-test and post-test questionnaires, the results showed that there were differences in understanding of the Canva application before and after the training. Before the training, 90% of participants knew about the Canva application and the rest did not know about the Canva application. After attending the training, my understanding of the Canva application increased. This is proven by 100% of participants answering correctly regarding the scope, function and benefits of Canva in creating graphic designs, posters and presentations. At the end of the service activities, assistance to the Rebo Village library in the form of grants for children's reading books, educational posters, bookcases and reading chairs was also provided to improve the reading culture as part of efforts to increase literacy in the Rebo Village community.